Use of mineral-resin composite fiber for reinforcing concrete

By using mineral-resin composite monofilaments in concrete, the shortcomings of existing concrete materials in terms of tensile strength and crack resistance are solved, uniform distribution of fibers and high mechanical properties are achieved, the temperature range of use is expanded, and CO2 emissions are reduced.

CN119630621APending Publication Date: 2025-03-14MICHELIN & CO (CIE GEN DES ESTAB MICHELIN)
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380057163.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-15
Filing Date
2023-06-14
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing concrete materials have shortcomings in tensile strength and crack resistance, and metal fibers are prone to sink, so the mechanical strength and use temperature of synthetic fibers are relatively limited.

Method used

The mineral-resin composite monofilament is used, including mineral wire other than glass wire embedded in the crosslinked resin, and is made by vacuum degassing, impregnation and ultraviolet irradiation to ensure uniform distribution of the fibers and high mechanical properties.

Benefits of technology

The uniform distribution of fibers in concrete is achieved, the tensile strength and crack resistance of concrete are improved, and the use temperature range of fibers is expanded, while reducing CO2 emissions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119630621A_ABST
    Figure CN119630621A_ABST
Patent Text Reader

Abstract

The present invention relates to a mineral-resin composite monofilament that can be used to reinforce concrete, the monofilament comprising mineral filaments other than glass embedded in a cross-linked resin, the monofilament having a diameter of 0.2 mm to 1.3 mm and a porosity of less than 2%. The invention also relates to a bobbin comprising a monofilament and to a method for obtaining said monofilament.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to mineral-resin composite fibers that can be used to reinforce concrete and a method for obtaining the mineral-resin composite fibers. Background Art

[0002] Concrete is arguably the most widely used building material today due to its high compressive strength, durability, longevity and resilience. Its properties make it the material of choice, especially in the fields of buildings, roads and engineering structures.

[0003] Concrete consists mainly of aggregates held together by a binder, most commonly Portland cement. In order to improve the properties of concrete, it is known to use additives such as ultrafine particles (e.g. silica fume), superplasticizers (also called water-reducing plasticizers) or metal, synthetic or mineral fibers.

[0004] Although very resistant to compression, concrete has low tensile strength and tension is often accompanied by the appearance of cracks. To overcome this problem, it is known to use reinforcing fibers. Due to their mechanical properties, metal fibers are particularly useful for reinforcing concrete. Therefore, they are very widely used to make concrete more ductile and improve its resistance to cracking.

[0005] However, metal fibers have the disadvantage of being sensitive to corrosion, which can be detrimental to the life of the concrete comprising such fibers. In addition, their density is generally greater than 7.7 and therefore they cannot be evenly distributed in concrete with a lower density (metal fibers tend to sink under the effect of gravity, or even under the effect of vibration when the concrete is vibrated to remove any air bubbles that may have formed during the pouring process).

[0006] To address this problem, it has been proposed to use synthetic fibers instead of metal fibers. However, the mechanical strength of these fibers (e.g. elastic (Young's) modulus, tensile strength) is not as good as that of metal fibers. In addition, their operating temperature (usually between 100°C and 160°C) is much lower than that of metal fibers (approximately between 600°C and 900°C), which may limit their use in certain applications.

[0007] Therefore, it would still be advantageous to have fibers that are corrosion resistant (to increase the service life of the concrete) and have improved mechanical properties (to improve crack resistance) compared to current non-metallic fibers. Summary of the invention

[0008] In the course of the research carried out, the applicant has surprisingly found that the above-mentioned problems can be solved by using specific mineral-resin composite fibers.

[0009] The Applicant has also observed many advantages obtained with the fibres according to the invention. Compared with the fibres of the concrete of the prior art, they are very easy to implement, in particular in the stage of mixing the various components of the concrete (easy dispersion), and in the stage of drying the concrete: since their density is close to that of the concrete, the fibres remain uniformly distributed in the concrete (they do not tend to sink like metal fibres whose density is greater than that of the concrete, nor to rise like synthetic fibres whose density is less than that of the concrete). The fibres of the invention also have a much higher maximum temperature of use than the synthetic fibres currently used. Moreover, and more generally, the use of the fibres according to the invention, due to their density and their reinforcing capacity, makes it possible, for the same reinforcing level, to reduce the overall emissions of CO2 considerably compared with the use of other fibres of the prior art.

[0010] The present invention therefore relates to a mineral-resin composite monofilament comprising mineral filaments other than glass filaments, said filaments being embedded in a cross-linked resin, having a diameter ranging from 0.2 mm to 1.3 mm and characterised in that the porosity of the monofilament is less than 2%.

[0011] The invention also relates to a bobbin comprising a monofilament according to the invention and to a method for producing a mineral-resin composite monofilament comprising mineral filaments other than glass filaments embedded in a crosslinked resin, the method comprising the following successive steps:

[0012] - forming a rectilinear arrangement of mineral threads other than glass threads and conveying this arrangement in the feed direction,

[0013] - degassing the mineral threads of the arrangement other than the glass threads by the action of a vacuum in a vacuum chamber,

[0014] - at the outlet of the vacuum chamber, after degassing, passing through a vacuum impregnation chamber to impregnate the mineral threads other than glass threads of the arrangement with a photocrosslinkable resin composition in a liquid state (referred to as "impregnating resin"), thereby obtaining a prepreg comprising mineral threads other than glass threads and the resin composition,

[0015] - passing the prepreg through a shaping die having a cross-section with a predetermined area and shape, so that it has the shape of a monofilament,

[0016] - Downstream of the die, the resin composition is polymerized under the action of ultraviolet rays in a UV irradiation chamber, the irradiation chamber comprising a tube transparent to ultraviolet rays, called an irradiation tube, through which the monofilaments to be formed are passed and through which a stream of inert gas flows, the running speed of the monofilaments through the irradiation chamber (denoted by V ir ) is greater than 50m / min, the irradiation time of the monofilament in the irradiation chamber (expressed as Dir ) is equal to or greater than 1.5s.

[0017] I-Definition

[0018] In the present application, unless expressly stated otherwise, all percentages (%) shown are percentages (%) by weight.

[0019] The expression "composition based on" is understood to mean that the composition comprises a mixture and / or in situ reaction products of the various components used, some of which are able and / or intended to react at least partially with one another during the various stages of manufacture of the composition; the composition may therefore be in a completely or partially crosslinked state, or in a non-crosslinked state.

[0020] In addition, any numerical interval represented by the expression "between a and b" means a numerical range extending from greater than a to less than b (i.e., excluding the end values ​​a and b), while any numerical interval represented by the expression "a to b" means a numerical range extending from a to b (i.e., including the strict end values ​​a and b). In the present application, when a numerical interval is represented by the expression "a to b", it is also preferably intended to represent the interval represented by the expression "between a and b".

[0021] All glass transition temperature "Tg" values ​​described herein are measured in a known manner by DSC (Differential Scanning Calorimetry) according to Standard ASTM D3418 (1999). BRIEF DESCRIPTION OF THE DRAWINGS

[0022] II-Brief description of the drawings

[0023] [ Figure 1 ] Figure 1 is a schematic diagram of a method for synthesizing a monofilament according to the present invention.

[0024] [ Figure 2 ] Figure 2 (For ease of understanding, it is not shown to scale) is a diagram showing a cross section of a monofilament according to the present invention. DETAILED DESCRIPTION

[0025] III-Description of the Invention

[0026] The present invention therefore relates to a monofilament (or fiber, the two terms being used in an equivalent manner) made of a mineral-resin composite material (abbreviated as "CMR"), comprising mineral threads other than glass threads embedded in a cross-linked resin (i.e. a resin that solidifies after cross-linking), having a diameter ranging from 0.2 mm to 1.3 mm, and characterized in that the porosity of the monofilament is less than 2%.

[0027] The expression "mineral threads other than glass threads" is understood to mean mineral threads that do not consist of glass or preferably do not comprise glass. Such threads are well known to those skilled in the art and include in particular basalt threads, wollastonite threads, etc. In the following, when reference is made to mineral threads, they will implicitly be mineral threads other than glass threads of the CMR.

[0028] As examples of mineral fibers other than glass fibers that can be used in the context of the present invention, mention may be made of basalt fibers "KVT400TEX14I-KV41" from Basaltex, "DR650_17_05" from Mafic, "BF811-1200" from Jumeisheng or Filva from Isomatex. TM Fibers. A person skilled in the art knows very well how to adapt dimensions to the surface of a thread so as to improve its compatibility with the resin used in the mineral-resin composite material, in particular with the help of compatibilizing agents of the silane type.

[0029] Preferably, the mineral threads other than glass threads are threads comprising basalt, preferably they are basalt threads. In this case, the mineral-resin composite material is a basalt-resin composite material (abbreviated as "CBR"). This preference applies to any case where CMR is mentioned.

[0030] Typically, the mineral filaments (preferably basalt filaments) are present in the form of a single multifilament fiber or a plurality of multifilament fibers combined together. In the case of a plurality of multifilament fibers combined together, the multifilament fibers are preferably substantially unidirectional. Each multifilament fiber may include tens, hundreds or even thousands of independent mineral filaments. The average diameter of these extremely fine independent filaments is typically and preferably 5 μm to 30 μm, more preferably 10 μm to 20 μm. The cross section of the independent filaments is preferably cylindrical.

[0031] Preferably, in the CMR monofilament of the present invention, the filaments of the monofilament are substantially parallel to each other. In particular, the degree of alignment of the mineral filaments is preferably such that more than 85% (number %) of the filaments have an inclination of less than 2.0 degrees, more preferably less than 1.5 degrees relative to the axis of the monofilament, the inclination (or misalignment) being measured as described in the above-mentioned publication of Thompson et al. It is also preferred that the CMR monofilament according to the present invention has no helical deformation, i.e. it is not twisted. In any case, the number of turns per meter of the CMR monofilament is less than 5, preferably less than 2, preferably less than 0.5, preferably from 0 to 0.5.

[0032] Preferably, the weight content of mineral fibers, preferably basalt fibers, in the CMR monofilaments is in the range of 65% to 85%, preferably 70% to 80%.

[0033] This weight content of mineral fibers is calculated using the ratio of the count of the initial mineral fibers to the count of the final CMR monofilament. The count (or linear density) is determined on at least three samples (each sample corresponding to a length of 50 m) by weighing the length; the count is given in tex (weight in grams of 1000 m of product - as a reminder, 0.111 tex is equal to 1 denier).

[0034] Furthermore, the volume fraction of mineral fibers, preferably basalt fibers, in the CMR monofilaments is advantageously in the range of 40% to 60%, preferably 45% to 55%.

[0035] The volume fraction of mineral fibers in the final CMR filament corresponds to the surface fraction of mineral fibers of the cross section of the CMR filament relative to the total area of ​​the cross section of the CMR filament. The surface fraction of mineral fibers can be determined in the same way as described below for measuring porosity.

[0036] Furthermore, the crosslinked resin accounts for 15 to 35% by weight, preferably 20 to 30% by weight, of the CMR (preferably CBR) monofilament of the present invention. Furthermore, the volume fraction of the resin in the CMR monofilament is advantageously in the range of 40 to 60%, preferably 45 to 55%. The weight percentage and volume fraction of the crosslinked resin can be obtained according to a method similar to that used to obtain the weight content and volume fraction of the above-mentioned mineral fibers.

[0037] By definition, the resins used are crosslinkable (ie curable) resins which can be crosslinked (cured) by any known method, in particular and preferably by UV (or UV-visible) radiation, preferably emitting in the spectrum ranging at least from 300 nm to 450 nm.

[0038] Here, the term "resin" or "resin composition" is understood to mean a resin in unmodified form, or any composition based on this resin and comprising at least one additive (i.e. one or more additives) before crosslinking. The term "crosslinked" resin is naturally intended to mean a resin that is cured (light-cured and / or heat-cured) in a state characteristic of "thermosetting" polymers (unlike "thermoplastic" polymers), in other words, in the form of a three-dimensional bond network.

[0039] Advantageously, the crosslinking resin is based at least on:

[0040] - a crosslinkable resin selected from the group consisting of vinyl ester resins (preferably urethane vinyl ester resins), epoxy resins, polyester resins and mixtures thereof,

[0041] - a cross-linking system, preferably comprising a photoinitiator, which is reactive to UV radiation above 300 nm.

[0042] As crosslinkable resins, polyester resins or vinyl ester resins are preferably used, more preferably vinyl ester resins. "Polyester" resins are understood in a known manner to mean resins of the unsaturated polyester type. As for the vinyl ester resins, they are well known in the field of composite materials.

[0043] Without this definition being limiting, the vinyl ester resin is preferably of the epoxy vinyl ester type. Even more preferably, a vinyl ester resin (especially of the epoxy type) is used which is at least partially based on phenolic resins (also called phenolics) and / or bisphenols (i.e. grafted onto structures of this type), i.e. preferably a vinyl ester resin based on phenolic resins, bisphenols or phenolic resins and bisphenols.

[0044] Preferably, the initial tensile modulus of the resin measured at 23°C is greater than 3.0 GPa, more preferably greater than 3.5 GPa.

[0045] Epoxy vinyl ester resins based on phenolic resins (the part between square brackets in the following formula I) correspond, for example, in a known manner to the following formula (I):

[0046]

[0047] Epoxy vinyl ester resins based on bisphenol A (the part between square brackets in the following formula (II)) ("A" serves to indicate that the product is prepared using acetone) correspond, for example, to the following formula:

[0048]

[0049] Epoxy vinyl esters of the phenolic and bisphenol type demonstrate excellent results. As examples of such resins, mention may in particular be made of the vinyl ester resins "ATLAC 590" and "ATLAC E-Nova FW 2045" from the company AOC (diluted with about 40% styrene) described in the above-mentioned patent applications EP-A-1074369 and EP-A-1174250. Epoxy vinyl ester resins are available from other manufacturers, for example AOC (USA - "Vipel" resins).

[0050] The crosslinking system for the impregnating resin (resin composition) preferably comprises a photoinitiator, said photoinitiator being sensitive (reactive) to UV radiation above 300 nm, preferably between 300 nm and 450 nm. The photoinitiator is used in a preferred content of 0.5% to 3%, more preferably 1% to 2.5%. Preferably, the resin crosslinking system also comprises a crosslinking agent, for example a crosslinking agent in a content of between 5% and 15% (% by weight of the impregnating composition), said crosslinking agent being as defined above.

[0051] Preferably, the photoinitiator is from the family of phosphine compounds, more preferably a bis(acyl)phosphine oxide (e.g. bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (“Omnirad 819” from IGM or “SpeedCure BPO” from Lambson)), or a mono(acyl)phosphine oxide (e.g. “Esacure TPO” from IGM), which phosphine compounds can be mixed with other photoinitiators, such as α-hydroxyketone type photoinitiators (e.g. dimethylhydroxyacetophenone (e.g. “Omnirad 1173” from IGM) or 1-hydroxycyclohexylphenyl ketone (e.g. “Omnirad 184” from IGM)), benzophenones (e.g. 2,4,6-trimethylbenzophenone (e.g. “Esacure TZT” from IGM)) and / or thioxanthone derivatives (e.g. isopropylthioxanthone (e.g. “Esacure Omnirad ITX” from IGM)).

[0052] The crosslinking agent is preferably selected from the family of triacrylates.

[0053] The diameter D of the CMR monofilament of the present invention is preferably in the range of 0.2 mm to 1.3 mm, preferably between 0.25 mm and 1.25 mm, more preferably between 0.3 mm and 1.2 mm, in particular between 0.4 mm and 1.1 mm.

[0054] This definition covers both substantially cylindrical (with a circular cross section) monofilaments and monofilaments of other shapes, such as elliptical monofilaments (with a more or less flat shape) or monofilaments with a rectangular cross section. In the case of non-circular cross sections, unless otherwise specifically stated, by convention D is the diameter known as the gap diameter, i.e. the diameter of an imaginary cylinder of revolution around the monofilament, in other words the diameter of the circumscribed circle around its cross section.

[0055] Furthermore, the length L of the CMR monofilament of the present invention is preferably in the range of 1 km to 60 km, preferably 10 km to 50 km. Monofilaments of this length are usually wound and stored in the form of a roll.

[0056] According to the invention, the porosity of the CMR monofilaments is advantageously less than 1%, preferably less than 0.5%. Advantageously, the porosity of the CMR monofilaments is between 0% and 2%, preferably between 0.01% and 1%, preferably between 0.05% and 0.5%.

[0057] Porosity can be measured by microscopy (e.g., scanning electron microscopy), preferably using area calculation software, such as the FIJI program. To perform the measurement, the following protocol is preferably performed:

[0058] - obtaining cross-linked CMR monofilaments,

[0059] - coating it with a cold coating resin, for example of the epoxy type, for example in a vacuum coating device (for example the CitoVac from the company Stuers),

[0060] - cutting the coated CMR monofilaments, for example using a hydraulic shear (for example "SH-5214" from the company Baileigh),

[0061] - polishing the cross section of the CMR monofilament, for example using a mechanical polisher such as from the company Mecapol, preferably to a final particle surface of 0.25 μm,

[0062] - Apply 1 nm to 4 nm of gold, for example using a gold sputter coater (e.g. from the company Cressington coater of series 108 or 208),

[0063] - observing the cross section of the CMR filament using a (15 kV) scanning electron microscope, preferably under vacuum, and

[0064] - Calculate the surface area percentage of porosity using an image processing program (eg FIJI). "Porosity" of a CMR filament means any gas (particularly air) or void space present within the CMR filament.

[0065] According to the present invention, the breaking stress Cr of the CMR monofilament is advantageously greater than 1250 MPa, more preferably greater than or equal to 1400 MPa. In particular, the breaking stress of the monofilament is preferably between 1250 MPa and 2000 MPa, preferably 1400 MPa to 1800 MPa.

[0066] Advantageously, the initial tensile modulus (expressed as E 23 ) (also called Young's modulus) is greater than 40 GPa, preferably greater than or equal to 42 GPa. In particular, the E 23 Preferably between 40 GPa and 70 GPa, preferably between 42 GPa and 65 GPa.

[0067] Mechanical tensile properties of CMR monofilaments (modulus E 23 , breaking stress Cr and breaking elongation Ar) can be measured in a known manner according to the protocol described in Section IV-1 below.

[0068] The glass transition temperature (expressed as Tg) of the crosslinked resin is preferably greater than 190° C., preferably greater than 195° C., in particular greater than 200° C. In the present application, unless otherwise specifically stated, the glass transition temperature is measured in a known manner, for example by DSC (Differential Scanning Calorimetry) in the second scan according to standard ASTM D3418 of 1999 (DSC apparatus "822-2" from Mettler Toledo; nitrogen atmosphere; the sample is first raised from ambient temperature (23° C.) to 250° C. (10° C. / min), then rapidly cooled to 23° C., and then finally recording the DSC curve with a ramp of 10° C. / min from 23° C. to 250° C.).

[0069] Preferably, the density (or mass per unit volume, in g / cm 3 The density is measured by a professional balance of the "PG503 DeltaRange" type from Mettler Toledo (at 23° C.); several centimeters of the sample are weighed in turn in air and immersed in ethanol, and the device's software then determines the average density from three measurements.

[0070] The invention also relates to a method for manufacturing filaments or fibers (the two terms can be used in an equivalent manner) made of a mineral-resin composite material (abbreviated as "CMR"), said method comprising the following successive steps:

[0071] - forming a rectilinear arrangement of mineral threads other than glass threads and conveying this arrangement in the feed direction,

[0072] - degassing the mineral threads of the arrangement other than the glass threads by the action of a vacuum in a vacuum chamber,

[0073] - at the outlet of the vacuum chamber, after degassing, passing through a vacuum impregnation chamber to impregnate the mineral threads other than glass threads of the arrangement with a photocrosslinkable resin composition in a liquid state (referred to as "impregnating resin"), thereby obtaining a prepreg comprising mineral threads other than glass threads and the resin composition,

[0074] - passing the prepreg through a shaping die having a cross-section with a predetermined area and shape, so that it has the shape of a monofilament,

[0075] - Downstream of the die, the resin composition is polymerized under the action of ultraviolet rays in a UV irradiation chamber, the irradiation chamber comprising a tube transparent to ultraviolet rays (referred to as an irradiation tube), through which the monofilaments to be formed are passed and through which a stream of inert gas flows, the running speed of the monofilaments through the irradiation chamber (denoted as V ir) is greater than 50m / min, the irradiation time of the monofilament in the irradiation chamber (expressed as D ir ) is equal to or greater than 1.5 s, at the end of which step is obtained a CMR monofilament according to the invention comprising mineral threads other than glass threads embedded in a crosslinking resin.

[0076] All the steps of the process of the invention (arranging, degassing, impregnation, shaping, polymerization, winding (where applicable) and cutting (where applicable)) are independently of one another known to the person skilled in the art, as are the materials used (multifilament fibers and resin composition); for example, they are described in either or both of the patent applications EP-A-1074369 and EP-A-1174250.

[0077] According to the invention, it will be recalled in particular that, before any impregnation of the fibers, an essential step of degassing the arranged fibers by the action of a vacuum must be carried out, in order in particular to improve the effectiveness of the subsequent impregnation and in particular to ensure the absence of air bubbles in the final composite monofilament.

[0078] After passing through the vacuum chamber, the mineral filaments, preferably basalt filaments, enter an impregnation chamber which is completely filled with impregnation resin and is therefore free of air: in this sense, this impregnation step may be called "vacuum impregnation".

[0079] The mould, known as a "shaping" mould, makes it possible to adjust the proportion of resin to mineral filaments (preferably basalt filaments) by having a cross section of a given size (usually and preferably circular or rectangular), while giving the prepreg the desired shape and thickness of the monofilament.

[0080] Advantageously, the diameter of the monofilaments leaving the shaping die ranges from 0.2 mm to 1.3 mm, preferably from 0.25 mm to 1.25 mm, preferably from 0.3 mm to 1.2 mm.

[0081] The polymerization or UV irradiation chamber has the function of polymerizing and cross-linking the resin under the action of ultraviolet rays.

[0082] The UV irradiation chamber includes one or more UV irradiators (or radiators). Advantageously, the irradiation chamber includes a plurality of UV irradiators arranged in a row around the irradiation tube, i.e., at least two (two or more than two) UV irradiators. Each UV irradiator generally includes one (at least one) UV lamp (preferably emitting in a spectrum of 200nm to 600nm) and a parabolic reflector, the focus of the parabolic reflector being the center of the irradiation tube; the linear power density provided is preferably between 2000 watts / m and 14000 watts / m. Still more preferably, the irradiation chamber includes at least three, in particular at least four rows of UV irradiators.

[0083] Even more preferably, the linear power density provided by each UV irradiator is between 2500 Watt / m and 12000 Watt / m, in particular in the range of 3000 Watt / m to 10000 Watt / m.

[0084] UV irradiators suitable for the method according to the invention are known to the person skilled in the art and are available, for example, from the company Dr. UV radiators equipped with "UVAPRINT" lamps (iron-doped high-pressure mercury lamps) are sold by AG (Germany) under the reference "1055LCP AM UK". The nominal (maximum) power of each radiator of this type is equal to about 13,000 Watts, the power output being adjustable in practice by means of a potentiometer between 30% and 100% of the nominal power.

[0085] The diameter of the irradiation tube (preferably made of glass) is preferably between 10 mm and 80 mm, more preferably between 20 mm and 60 mm.

[0086] Between the shaping die and the final receiving support, the tension to which the mineral fibers are subjected is preferably maintained at a moderate level, preferably between 0.2 cN / tex and 2.0 cN / tex, more preferably between 0.3 cN / tex and 1.5 cN / tex; in order to control this, these tensions can be measured directly at the exit of the irradiation chamber, for example by means of a suitable tensiometer known to a person skilled in the art.

[0087] The final CMR monofilament thus formed by passing through the UV irradiation chamber (where the resin is now in a solid state) is then recovered, for example, on a take-up drum, where it can be wound up to a very long length. Thus, the method may include a winding step for storing the monofilament after it has passed through the UV irradiation chamber.

[0088] The monofilament can be cut to any usable length depending on the intended use.

[0089] For use in reinforcing concrete, the monofilaments obtained from the irradiation chamber (optionally after storage) can advantageously be cut to obtain monofilaments having a length in the range of 5 mm to 85 mm, preferably 10 mm to 80 mm, for example 15 mm to 60 mm. In this case, the length / diameter ratio of the monofilaments is advantageously in the range of 10 to 110, preferably 20 to 90, preferably 25 to 80, preferably 30 to 70.

[0090] Particularly advantageously, the method of the present invention for producing CMR monofilaments comprises the following essential steps:

[0091] - The running speed of the monofilament through the irradiation chamber (V ir ) greater than 50m / min;

[0092] - The running time of the monofilament through the irradiation chamber (D ir ) is equal to or greater than 1.5s and equal to or less than 10s;

[0093] The irradiation chamber comprises a tube transparent to UV rays (for example a quartz tube or preferably a glass tube), called the irradiation tube, through which the monofilament to be formed runs and through which a flow of an inert gas (preferably nitrogen) is passed.

[0094] These combined steps enable the improved properties of the CMR monofilaments of the present invention to be achieved, namely in particular improved Tg, elongation Ar and modulus (E and E') properties.

[0095] In particular, in the case where no inert gas (eg nitrogen) purging is used in the irradiation tube, it is observed that the above-mentioned properties deteriorate very rapidly during the manufacturing process, so that industrial performance can no longer be guaranteed.

[0096] In addition, if the irradiation time D of the monofilament in the irradiation chamber is ir If the irradiation time D of the monofilament in the irradiation chamber is too short (less than 1.5 s), many tests show that the resin is not fully cross-linked, resulting in poor mechanical properties (including breaking stress and flexural strength). ir If it is too long (eg greater than 10 s), this will increase the risk of the resin boiling, thereby creating more voids and deteriorating the mechanical properties (including fracture stress).

[0097] It is thus understood that, thanks to the combination of the steps of the method according to the invention, in particular thanks to the step of degassing the arranged mineral threads in a vacuum chamber by the action of a vacuum and in an irradiation tube through which a flow of inert gas passes at the above mentioned speed V ir and the above irradiation time D ir The step of polymerization is performed to obtain a CMR monofilament with a porosity of less than 2% and a breaking stress of more than 1250 MPa.

[0098] It is also observed that high irradiation speed V ir (greater than 50 m / min, preferably between 50 m / min and 150 m / min) on the one hand facilitates an excellent degree of alignment of the mineral threads within the CMR monofilament and on the other hand facilitates better maintenance of the vacuum in the vacuum chamber, thereby significantly reducing the risk of a certain amount of impregnation resin migrating back from the impregnation chamber into the vacuum chamber and thus facilitates a better impregnation quality.

[0099] Preferably, the speed V ir Between 50 m / min and 150 m / min, more preferably in the range of 60 m / min to 120 m / min.

[0100] Preferably, the irradiation time D irBetween 1.5 s and 10 s, more preferably in the range of 2 s to 5 s.

[0101] The invention also relates to a reel comprising a monofilament according to the invention (or a monofilament obtainable by a method according to the invention). The reel allows the storage of CMR (preferably CBR) monofilaments before their use (e.g. before their cutting), e.g. for use as concrete reinforcing fibers.

[0102] A subject matter described herein is a CMR (preferably CBR) monofilament obtainable by a method according to the invention, preferably according to which:

[0103] - The running speed of the monofilament through the irradiation chamber (V ir ) greater than 50m / min;

[0104] - The running time of the monofilament through the irradiation chamber (D ir ) is equal to or greater than 1.5s and equal to or less than 10s;

[0105] the irradiation chamber comprises a tube transparent to ultraviolet rays (for example a quartz tube or preferably a glass tube), called the irradiation tube, through which the monofilament to be formed is passed and through which a flow of an inert gas (preferably nitrogen) is passed,

[0106] The diameter of the CMR monofilaments ranges from 0.2 mm to 1.3 mm, preferably from 0.25 mm to 1.25 mm, preferably from 0.3 mm to 1.2 mm.

[0107] Thus, the CMR monofilaments obtainable by the method according to the invention comprise mineral filaments other than glass filaments, preferably basalt filaments, impregnated in a crosslinked resin, having a diameter ranging from 0.2 mm to 1.3 mm and a porosity of less than 2%. All the above characteristics of the monofilaments according to the invention also apply to the monofilaments obtainable by the method according to the invention. In particular, taking into account the specific steps of the method according to the invention, the monofilaments advantageously have a porosity of less than 1%, preferably less than 0.5%, and / or a breaking stress greater than 1250 MPa, preferably greater than or equal to 1400 MPa, and / or an initial tensile modulus of the monofilament measured at 23° C. (expressed as E ) greater than 40 GPa, preferably greater than 42 GPa. 23 ).

[0108] Another subject matter described herein is a tow comprising a plurality of CMR (preferably CBR) monofilaments according to the invention (or obtainable by a process according to the invention) and at least one element for holding together the cut monofilaments, the monofilaments being cut to a length in the range of 5 to 85 mm, preferably 10 to 80 mm, preferably 15 to 60 mm. Preferably, the holding element is a rupturable film, such as a tearable, dispersible water-soluble film. Preferably, at least one holding element is a water-soluble thread.

[0109] Advantageously, the retaining element is a water soluble film, preferably made of a material selected from polyvinyl alcohol (PVA) or any water soluble or bioplastic polymer, such as a bioplastic derived from milk casein.Preferably, at least one water soluble film is made of a material selected from polyvinyl alcohol.

[0110] The tow according to the invention advantageously comprises a number of cut filaments in the range of 300 to 20,000.

[0111] The monofilaments constituting the tow may have the same or different sizes. For example, the tow may include monofilaments having different lengths, diameters and / or length-to-diameter ratios. Advantageously, the tow includes monofilaments according to the invention whose lengths and diameters differ from each other by no more than 10%, preferably by no more than 3%.

[0112] As indicated above, the monofilaments according to the invention can be used in particular as an additive to concrete. Therefore, the subject matter described herein is also the use of at least one CMR (preferably CBR) monofilament according to the invention (or obtainable by a method according to the invention) or the above-mentioned tow for reinforcing concrete and / or reducing the weight of concrete and / or reducing or preventing cracking of concrete, the monofilaments being cut to a length in the range of 5 mm to 85 mm, preferably 10 mm to 80 mm, preferably 15 mm to 60 mm.

[0113] A subject also described herein is a concrete comprising a plurality of cut CMR (preferably CBR) monofilaments according to the invention (or obtainable by a method according to the invention), the monofilaments being cut to a length ranging from 5 mm to 85 mm, preferably from 10 mm to 80 mm, preferably from 15 mm to 60 mm. The concrete can be prepared by any technique known to a person skilled in the art.

[0114] Advantageously, the volume content of the monofilaments according to the invention in the concrete according to the invention is in the range from 0.1% to 6%, for example from 0.1% to 1.5% for so-called "conventional" concrete (for example of type BPS C40 / 50XA3), or from 1.5% to 6% for ultra-high performance fiber reinforced concrete (UHPFRC).

[0115] Examples of the manufacture of CMR monofilaments according to the invention and their use for the reinforcement of concrete.

[0116] Attached Figure 1 An example of an apparatus 10 for producing CMR, preferably CBR, monofilaments according to the invention is schematically shown in a very simple manner.

[0117] In this figure, a reel 11a can be seen, which in the example shown comprises basalt fibers 11b (in multifilament form). The reel is continuously unwound by a drive, thereby producing a rectilinear arrangement 12 of these fibers 11b. Usually, the reinforcing fibers are delivered as "rovings", i.e. groups of fibers already wound in parallel on a reel; for example, a basalt fiber sold by Basaltex under the name "KVT250TEX17I-KV41" is used, whose count is equal to 250 tex (as a reminder, 1 tex = 1 g / 1000 m of fiber). For example, the traction applied by the rotating receiver 26 will advance the fibers in parallel and advance the CBR monofilaments along the entire length of the device 1.

[0118] The arrangement 12 is then passed through a vacuum chamber 13 (connected to a vacuum pump (not shown)) arranged between an inlet pipe 13a and an outlet pipe 13b leading to an impregnation chamber 14, the two pipes preferably having rigid walls, for example having a minimum cross-section that is larger than the total cross-section of the fibers (typically twice as large) and a length that is much larger than the minimum cross-section (typically 50 times as large).

[0119] As already taught in the above-mentioned patent application EP-A-1174250, the use of tubes with rigid walls for the inlet to the vacuum chamber and the outlet from the vacuum chamber and for the transfer from the vacuum chamber to the impregnation chamber has proven to be compatible with high throughput rates of the fibers through the openings without breaking the fibers and also to ensure adequate sealing. Taking into account the running speed of the fibers and the length of the tube, it is necessary (if experimentally necessary) to find the maximum flow cross-section that still allows adequate sealing, taking into account the total cross-section of the fibers to be treated. Typically, the vacuum in the chamber 13 is, for example, about 0.1 bar and the length of the vacuum chamber is about 1 meter.

[0120] On leaving the vacuum chamber 13 and the outlet pipe 13b, the arrangement 12 of fibers 11b passes through an impregnation chamber 14 comprising a feeding tank 15 connected to a metering pump (not shown) and a sealed impregnation tank 16 completely filled with an impregnation composition 17 based on a curable resin of the vinyl ester type (e.g. " E-Nova FW2045"). As an example, the composition 17 also contains (in a weight content of 1% to 2%) a photoinitiator suitable for UV irradiation and / or UV-visible irradiation, for example bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide ("Omnirad 819" from the company IGM), which is subsequently treated with the composition. It can also contain (for example about 5% to 15%) a crosslinker, for example tris(2-hydroxyethyl)isocyanurate triacrylate ("SR 368" from the company Sartomer). Of course, the impregnation composition 17 is in a liquid state.

[0121] Preferably, the impregnation chamber is several meters long, for example between 2 m and 10 m in length, in particular between 3 m and 5 m in length.

[0122] Thus, a prepreg comprising, for example (in wt. %) 65 to 75% solid fibres 11 b and the remainder (25 to 35%) formed by a liquid impregnation matrix 17 leaves the impregnation chamber 14 in a sealed outlet pipe 18 (still under rough vacuum).

[0123] The prepreg is then passed through a shaping device 19 comprising at least one shaping die 20, whose channel (not shown here) is, for example, circular, rectangular or even conical, suitable for the specific implementation conditions. As an example, the channel has a circular minimum cross section, and the diameter of its downstream orifice is slightly larger than the diameter of the target monofilament. The length of the die is usually at least 100 times the minimum dimension of the minimum cross section. Its purpose is to give the finished product a good dimensional accuracy, and it can also be used to meter the content of fiber relative to resin. According to a possible alternative form of embodiment, the die 20 can be directly incorporated into the impregnation chamber 14, so that, for example, there is no need to use an outlet pipe 18.

[0124] Preferably, the shaped area is several centimeters long, for example a length between 5 cm and 50 cm, in particular between 5 cm and 20 cm.

[0125] By means of the shaping devices (19, 20), a "liquid" composite monofilament 21 is obtained (liquid in the sense that its impregnation resin is still liquid), the cross-sectional shape of which is preferably substantially circular.

[0126] Then, at the outlet of the shaping device (19, 20), the liquid composite monofilament 21 obtained in this way is polymerized by passing through a UV irradiation chamber (22) comprising a sealed glass tube (23) through which the composite monofilament travels; the tube, which is generally a few centimeters in diameter (for example 2 to 3 cm), is irradiated by a plurality (here for example 4) of UV irradiators (24) arranged in a row at a short distance (a few centimeters) from the glass tube (from Dr. "UVAprint" lamp with a wavelength of 200nm to 600nm).

[0127] Preferably, the irradiation chamber is several meters long, for example between 2m and 15m in length, in particular between 3m and 10m in length.

[0128] In this example, the irradiation tube (23) has a nitrogen gas flow flowing through the irradiation tube (23).

[0129] The irradiation conditions are preferably adjusted so that at the outlet of the impregnation chamber the temperature of the CMR filaments measured at their surface (eg by a thermocouple) is greater than the Tg of the crosslinked resin (in other words greater than 190°C) and more preferably less than 270°C.

[0130] After the resin polymerizes (cures), the CBR filaments (25), now in a solid state and travelling in the direction of arrow F, then arrive at a final receiving reel (26).

[0131] Finally, if Figure 2 As shown very simply, the finished composite material block manufactured is obtained in the form of a continuous very long CBR monofilament (25) whose individual basalt threads (251) are uniformly distributed throughout the volume of the cured resin (252). Its diameter is for example equal to about 0.5 mm.

[0132] Due to the above operating conditions, the process of the present invention can be carried out at a high speed greater than 50 m / min, preferably between 50 m / min and 150 m / min, more preferably in the range of 60 m / min to 120 m / min.

[0133] The continuous CBR monofilament (25) can be cut to a given length ( 100 mm) by any method known to those skilled in the art, such as using a hydraulic shear (e.g. "SH-5214" from Baileigh). Figure 1 45 mm). This step can be carried out directly at the exit of the irradiation chamber (23). It can also be carried out after the monofilaments are packaged on the final receiving reel (26). In this case, it is preferred to unwind the monofilaments from the reel from the end of the monofilaments that is axially most toward the outside of the reel, so as to avoid spiral deformation of the monofilaments. In fact, if the monofilaments are unwound from the reel from the end of the monofilaments that is axially most toward the inside of the reel, this will cause the monofilaments to be spirally deformed, which will be unfavorable to the breaking stress.

[0134] IV - Examples

[0135] IV-1 Measurements and Tests Used

[0136] Porosity was measured according to the following protocol:

[0137] - obtaining cross-linked CBR monofilaments,

[0138] - coating it with a cold coating resin of epoxy type in a vacuum coating device (CitoVac from the company Stuers),

[0139] - cutting the coated CBR monofilaments using a hydraulic shear (SH-5214 from the company Baileigh),

[0140] - polishing of the cross-section of the CBR monofilaments to a final particle surface of 0.25 μm using a mechanical polisher from the company Mecapol,

[0141] -Using a gold sputtering coater (from the company Series 108 or 208 Cerssington coaters) apply 1nm to 4nm of gold,

[0142] - Observation of cross sections of CBR monofilaments using a scanning electron microscope (15 kV) under vacuum, and

[0143] - Calculate the percentage surface area of ​​pores (% Porosity = Area of ​​pores / (Area of ​​pores + Area of ​​fibers + Area of ​​cross-linked resin)) using an image processing program (eg FIJI).

[0144] According to standard ASTM D2343, the tensile tests were carried out at a temperature of 23° C. on the coated (i.e. ready-to-use) CBR monofilaments using an “INSTRON” model 5944 tensile tester (supplied with the tensile tester). UNIVERSAL software) to measure the tensile mechanical properties (modulus E 23, breaking stress Cr and breaking elongation Ar). Prior to the measurement, the filaments were subjected to preconditioning (storing the filaments for at least 24 hours in a standard atmosphere according to European standard DIN EN 20139 (temperature of 23°C ± 2°C; relative humidity of 50% ± 5%)). In order to prevent damage to the basalt reinforcement when the sample is clamped in the jaws of the tensile tester, the end pieces are connected as follows (material: cardboard, 50 mm long; adhesive used: Loctite EA 9483 (two-component epoxy resin)). The surfaces of the two opposing end pieces are coated with adhesive, as are the reinforcements, thereby limiting any "dry areas" (areas without adhesive) as much as possible. The end pieces are kept in an appropriate position in a fixture with the specimen size for the curing time (12 h at 23°C), with weights on the end pieces to ensure good end piece / reinforcement contact. The tensile modulus is determined by linear regression of the stress versus strain curve (between 0.1% strain and 0.6% strain). The strain is recorded by an extensometer MultiXtens 1995DA801. The 260 mm specimens tested were pulled at a nominal speed of 5 m / min under a preload of 0.5 MPa before the test (reference length 50 mm, distance between jaws: 150 mm). All results given are the average of 5 measurements.

[0145] IV-2 Testing of Monofilaments

[0146] CBR monofilaments (M1 to M3) were manufactured according to the above method, wherein the running speed V of the monofilaments in the irradiation chamber was ir is 100m / min, and the irradiation time of the monofilament in the irradiation chamber is D ir The irradiation chamber was 2.4 s and the length of the irradiation chamber was 4 m. The resin composition used was based on a vinyl ester resin ("ATLAC E-NOVA FW2045" from the company), a triacrylate hardener ("SR 368" from the company Sartomer) and a photoinitiator ("Omnirad 819" from the company IGM). The basalt filaments of the monofilaments M1, M2 and M3 were "KVT250TEX17I-KV41" filaments from Basaltex, respectively. Table 1 below shows the diameter and tex of the monofilaments and their physical and mechanical properties.

[0147] [Table 1]

[0148] M1 M2 M3 Diameter(mm) 0.5 0.61 0.75 Basalt fiber tex (g / km) 250 400 600 Basalt fiber / resin weight ratio 69 / 31 71 / 29 70 / 30 Porosity(%) 0.7 1.7 1.5 Fracture stress (MPa) 1405 1550 1523 Young's modulus(GPa) 42 45 44

[0149] The porosity and breaking stress of these monofilaments are compared with prior art reinforcing fibers for concrete. It is observed that these prior art fibers systematically have a porosity greater than 2% and a breaking stress less than or equal to 1250 MPa.

[0150] Due to the low porosity and high breaking stress, the monofilaments of the invention are able to improve the crack resistance of concrete.

[0151] Thus, it was found that the monofilaments according to the invention offer an improved compromise of properties between, in particular, mechanical strength, corrosion resistance, processability (in particular dispersion during mixing, processing temperature and maintenance of homogeneity during drying of the concrete).

Claims

1. A mineral-resin composite monofilament comprising mineral threads other than glass threads embedded in a cross-linked resin, having a diameter ranging from 0.2 mm to 1.3 mm, characterized in that The porosity of the monofilaments is less than 2%.

2. The monofilament according to claim 1, wherein the diameter of the monofilament is in the range of 0.25 mm to 1.25 mm, preferably 0.3 mm to 1.2 mm.

3. The monofilament according to any one of the preceding claims, wherein The mineral filaments other than the glass filaments account for 65 to 85 wt %, preferably 70 to 80 wt %, of the monofilament, and the crosslinking resin accounts for 15 to 35 wt %, preferably 20 to 30 wt % of the monofilament.

4. The monofilament according to any one of the preceding claims, wherein The mineral threads other than the glass threads each have an average diameter in the range of 5 μm to 30 μm, more preferably 10 μm to 20 μm.

5. The monofilament according to any one of the preceding claims, wherein The cross-linked resin is based on at least: - a crosslinkable resin selected from the group consisting of vinyl ester resins, epoxy resins, polyester resins and mixtures thereof, - a cross-linking system comprising a photoinitiator, which is reactive to UV radiation above 300 nm.

6. The monofilament according to any one of the preceding claims, wherein The mineral yarns other than glass yarns are yarns containing basalt, preferably basalt yarns.

7. The monofilament according to any one of the preceding claims, having a length in the range of 1 km to 60 km, preferably 10 km to 50 km.

8. Monofilament according to any of the preceding claims, having a porosity of less than 1%, preferably less than 0.5%.

9. Monofilament according to any one of the preceding claims, having a breaking stress greater than 1250 MPa, preferably greater than or equal to 1400 MPa.

10. The monofilament according to any one of the preceding claims, wherein The monofilament measured at 23°C is denoted as E 23 The initial tensile modulus is greater than 40 GPa, preferably greater than 42 GPa.

11. A reel comprising the monofilament according to any one of claims 1 to 10.

12. A method for producing a mineral-resin composite monofilament according to any one of claims 1 to 10, comprising mineral filaments other than glass filaments embedded in a crosslinked resin, the method comprising the following successive steps: - forming a rectilinear arrangement of mineral threads other than glass threads and conveying this arrangement in the feed direction, - degassing the mineral threads of the arrangement other than the glass threads by the action of a vacuum in a vacuum chamber, - at the outlet of the vacuum chamber, after degassing, passing through a vacuum impregnation chamber in order to impregnate the mineral threads other than glass threads arranged with a photocurable resin composition called "impregnation resin" in a liquid state, so as to obtain a prepreg comprising mineral threads other than glass threads and the resin composition, - passing the prepreg through a shaping die having a cross-section with a predetermined area and shape so as to give it a monofilament shape, - Downstream of the die, the resin composition is polymerized under the action of ultraviolet rays in a UV irradiation chamber, the irradiation chamber comprising a tube transparent to ultraviolet rays, called an irradiation tube, through which the monofilaments to be formed are passed and through which a stream of inert gas flows, the running speed of the monofilaments through the irradiation chamber (denoted by V ir ) is greater than 50m / min, the irradiation time of the monofilament in the irradiation chamber (expressed as D ir ) is equal to or greater than 1.5s.

13. The method according to claim 12, characterized in that The diameter of the monofilaments ranges from 0.2 mm to 1.3 mm, preferably from 0.25 mm to 1.25 mm, preferably from 0.3 mm to 1.2 mm.

14. The method according to any one of claims 12 and 13, characterized in that The mineral yarns other than glass yarns are yarns containing basalt, preferably basalt yarns.

Citation Information

Patent Citations

  • Method for manufacturing highly stressed composite pieces

    EP1074369A1

  • Continuous resin impregnation of very long fibres for the manufacturing of elongated composite elements

    EP1174250A1